2013
DOI: 10.1002/lary.24425
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dexmedetomidine on noise‐induced hearing loss

Abstract: Dexmedetomidine displayed protective effects against NIHL in this animal model, suppressing activation of the sympathetic nervous system and improving CoBF. These findings could have clinical relevance and deserve further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…Another factor contributing to the inconsistency between our results and those reported in the Wang et al study is that the anesthetic dexmedetomidine (S-enantiomer of medetomidine - used in our study) has been found to be protective against noise-induced hearing loss [ 46 , 47 ]. Overall, Wang et al’s results were strong in comparison to findings from several other trials, which demonstrated only a moderate protective effect (i.e., slightly more pronounced than the present results) of glucocorticoids after noise exposure in guinea pigs [ 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 75%
“…Another factor contributing to the inconsistency between our results and those reported in the Wang et al study is that the anesthetic dexmedetomidine (S-enantiomer of medetomidine - used in our study) has been found to be protective against noise-induced hearing loss [ 46 , 47 ]. Overall, Wang et al’s results were strong in comparison to findings from several other trials, which demonstrated only a moderate protective effect (i.e., slightly more pronounced than the present results) of glucocorticoids after noise exposure in guinea pigs [ 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 75%
“…Protection from temporary threshold shift (TTS) under sedation/anesthesia might be due to a diminished sympathetic influence [ 46 ]. After noise exposure, dexmedetomidine displayed protective effects against NIHL [ 47 ]. In mice, manipulation of adrenergic inputs to the cochlea confirmed that SNS regulates cochlear blood flow in response to intense loud sound exposure [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…old) were used. All guinea pigs passed a click-evoked ABR hearing screening and had hearing thresholds ≤ 20 dB SPL ( Wen, Xiao, Bai, & Xu, 2013 ), and were without any history of noise exposure or apparent developmental disorders. All guinea pigs were placed under sedation using an initial dose of intramuscular injection of a mixture of Zoletil (30 mg/kg, Virbac, Carros, France) and Xylazine (10 mg/kg, Bayer, Leverkusen, Germany) before audiological testing.…”
Section: Methodsmentioning
confidence: 99%